2022
DOI: 10.1145/3564281
|View full text |Cite
|
Sign up to set email alerts
|

On the Robustness of Aspect-based Sentiment Analysis: Rethinking Model, Data, and Training

Abstract: Aspect-based sentiment analysis (ABSA) aims at automatically inferring the specific sentiment polarities towards certain aspects of products or services behind the social media texts or reviews, which has been a fundamental application to the real-world society. Within recent decade, ABSA has achieved extraordinarily high accuracy with various deep neural models. However, existing ABSA models with strong in-house performances may fail to generalize to some challenging cases where the contexts are variable, i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…However, observations have shown that aspect-based sentiment analysis models trained on a dataset from one domain do not generalize well to another dataset belonging to another domain [23]. In [24], the authors enhanced the aspect-based sentiment analysis robustness by improving the model, data, and training. They tested data from different domains.…”
Section: Arabic Dataset and Opinion Mining Methodsmentioning
confidence: 99%
“…However, observations have shown that aspect-based sentiment analysis models trained on a dataset from one domain do not generalize well to another dataset belonging to another domain [23]. In [24], the authors enhanced the aspect-based sentiment analysis robustness by improving the model, data, and training. They tested data from different domains.…”
Section: Arabic Dataset and Opinion Mining Methodsmentioning
confidence: 99%
“…Graph convolutional networks (GCNs), which are an adaptation of the CNNs for handling unstructured data, can facilitate the handling of dependency trees. Zhang et al [22] built a universal-syntax GCN over the syntactic dependencies with labels to achieve the goal of navigating richer syntax information for the best aspect-based SA robustness. With the development of deep learning, several strategies and approaches have been proposed for improving the ability of CNNs to extract sentiment features [23].…”
Section: Cnns and Resnets In Sa Tasksmentioning
confidence: 99%
“…The margin 𝛾 can be obtained by calculating the length of the projection of the difference between the support vectors and the 𝐰 vector in Equation (12).…”
Section: Svm Classification Modelmentioning
confidence: 99%
“…Shi et al (2022) addressed limitations in structured sentiment analysis by proposing a novel labeling strategy and a graph attention network-based model, significantly surpassing previous state-of-the-art models [11]. Fei et al (2022) focused on enhancing the robustness of ABSA models through multi-faceted improvements, spanning model design, data augmentation, and advanced training strategies [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation